Analysis of genes encoding high-antigenicity polypeptides in three serotypes of Miamiensis avidus. Issue 2 (April 2018) - Motokawa, Shogo; Narasaki, Yukie; Song, Jun-Young; Yokoyama, Yoshihiro; Hirose, Euichi; Murakami, Shoko; Jung, Sung-Ju; Oh, Myung-Joo; Nakayama, Kei; Kitamura, Shin-Ichi
Abstract: The ciliate Miamiensis avidus causes scuticociliatosis in Japanese flounder Paralichthys olivaceus . We previously reported three serotypes of this ciliate distinguishable by serotype-specific antigenic polypeptides (serotype I, 30 kDa; serotype II, 38 kDa; serotype III, 34 kDa). In this study, we determined the localization site of the serotype-specific polypeptides in the ciliate and determined the genes encoding the polypeptides, using the isolates IyoI (serotype I), Nakajima (serotype II), and Mie0301 (serotype III). SDS-PAGE and immunoblot analysis of cilia, membrane proteins, and cytoskeletal elements of the ciliates revealed that the polypeptides were abundant in the former two. Scanning electron microscopy of ciliates immobilized by homologous antiserum showed morphological changes in the cilia. These evidences suggested that the polypeptides were ciliary membrane immobilization antigens. The ciliary genes identified showed low identity scores—< 51.5% between serotypes. To differentiate the serotypes, we designed serotype-specific PCR primer sets based on the DNA sequences. The PCR-based serotyping results were completely consistent with conventional serotyping methods (immobilization assay and immunoblot analysis). Twenty of 21 isolates were classified as either serotype I or II, and one isolate was undistinguishable. The combination of species-specific PCR previously reported and three serotype-specific PCR could be useful for identifying, serotyping, and surveillance for occurrences of new serotypes of M. avidus . Highlights: Three serotypes of M. avidus were reported in Japan and Korea. Serotype-specific polypeptides were identified as ciliary membrane proteins. The nucleotide sequences of ORFs were determined. Serotype-specific PCR revealed that the pandemic serotypes were serotype I and II.